Judicial compassion - commentary on 'Compassion and the Law: A Judicial Perspective' - Feenan, D; Bedford, D; Herring, J (LexisNexis (Jordan Publishing), 2015)
This article provides a commentary on the article by District Judge Anselm Eldergill 'Compassion and the law: a judicial perspective' published in the previous issue of the Elder Law Journal at [2015] Eld LJ 268. Recognising the importance of Judge Eldergill's contribution to consideration of compassion to the judicial role and law, the article has three aims; to: (1) contextualise the significance of Judge Eldergill's contribution with wider reference to the law and associated literature; (2) develop consideration of the place of compassion as a judicial quality; and (3) analyse the current place and potential for compassion as a basis for judicial decision. The article approves Judge Eldergill's reasoning for compassion as an 'instrument of justice', while also developing cautious arguments for the place of compassion in the jurisdiction and jurisprudence of both the Court of Protection and High Court.